Pimavanserin: A Novel Antipsychotic With Potentials to Address an Unmet Need of Older Adults With Dementia-Related Psychosis - Ismaeel Yunusa; Marie Line El Helou; Saud Alsahali (Frontiers Media S.A., 2020)
Dementia affects more than 40 million people worldwide. When it is accompanied by psychosis, symptom management is especially challenging. Although no drug has been approved by the US Food and Drug Administration (FDA) for psychosis in patients with dementia, atypical antipsychotics are used off-label in severe cases in patients who do not respond to non-pharmacological interventions. However, antipsychotic use in elderly patients with dementia-related psychosis (DRP) is associated with adverse reactions including motor function disorders, cognitive impairment, cerebrovascular events, and increased risk of death. In 2017, the US FDA granted breakthrough therapy designation to the new antipsychotic pimavanserin for the treatment of DRP. Topline result of the pivotal phase III HARMONY (NCT03325556) trial suggests that pimavanserin reduces the relapse of psychosis by 2.8-folds compared to placebo. This favorable result may open path for the potential approval of pimavanserin in DRP. In this review, we discuss the pharmacological activity, clinical efficacy and safety of pimavanserin as a novel atypical antipsychotic with potentials to address the unmet needs of older adults with DRP.